If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + 54 = x + 60 Reorder the terms: 54 + 7x = x + 60 Reorder the terms: 54 + 7x = 60 + x Solving 54 + 7x = 60 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 54 + 7x + -1x = 60 + x + -1x Combine like terms: 7x + -1x = 6x 54 + 6x = 60 + x + -1x Combine like terms: x + -1x = 0 54 + 6x = 60 + 0 54 + 6x = 60 Add '-54' to each side of the equation. 54 + -54 + 6x = 60 + -54 Combine like terms: 54 + -54 = 0 0 + 6x = 60 + -54 6x = 60 + -54 Combine like terms: 60 + -54 = 6 6x = 6 Divide each side by '6'. x = 1 Simplifying x = 1
| -6-14v=-17v | | Y=-16x^2+15x+5 | | 2x-4+3x+5+2x+4=180 | | 2x+4-x-9+7+3x-4= | | 12x-13y=2 | | X^2+(2-k)x-2k=0 | | 12+7r=5+8r | | 2.5p=12.5 | | 4+7a=-8a-11 | | 13+20s=15s+3s-11 | | 9x+5=7x+35 | | 3(4p+7)-9+16= | | 3timesn-5=25 | | -2x+4x=5x+6 | | 6x+52=12x-8 | | x^4-7x^2-44= | | 3*n-5=25 | | 4(z-1)+16=24 | | -40a+28=12 | | 3xn-5=25 | | 0.75p+3=5.88 | | -9-4a=a-2a | | 3y+3=2y-3 | | b/4+9=14 | | (2.72)+2y=3.5 | | 1+9b+6-2b= | | 3r+2=20 | | -40+28=12 | | 9t+4.8=17.4 | | -x-17=-40 | | x-2(2+4)=10 | | K=3M-7forM |